LEXICOGRAPHY: SYNONYMS, ANTONYMS AND HOMONYMS IN ENGLISH - Norpulatov Dilshod (Ta’lim innovatsiyasi va integratsiyasi, 2026)
ABSTRACT: Lexical relations such as homonymy, synonymy, and antonymy constitute the backbone of meaning organization in English and many other languages. Homonyms are words that share either sound, spelling, or both while diverging in meaning and grammatical distribution. They are traditionally divided into three primary types: (1) homonyms proper, which are identical in both pronunciation and orthography (bank meaning a riverbank versus a financial institution); (2) homophones, which share pronunciation but differ in spelling (knight versus night); and (3) homographs, which share spelling but differ in pronunciation or sense (bow [the front of a ship] versus bow [to bend]. Further subclassifications consider part-of-speech alignment—lexical homonyms belong to the same grammatical category, whereas lexico-grammatical homonyms cross categories (left the direction versus left the past of leave)—and paradigm overlap, distinguishing full homonyms whose inflectional paradigms match (match → matches) from partial homonyms whose paradigms only partially coincide (lie → lying vs. lied). Synonymy involves distinct lexical items that convey overlapping denotative content but differ in distributional frequency, stylistic register, intensity, duration, or contextual suitability.